Government Expenditure on Education: How Effective and Efficient is It? - Solihin, Achmad; Mursinto, Djoko; Sugiharti, Lilik (Modern Perspectives in Economics, Business and Management Vol. 8, 2021)
The purpose of this study is to investigate and analyze the efficiency and effectiveness of local government expenditure in the education sector at district and city levels of East Java from 2007 to 2014. Furthermore, this study evaluates the impacts of local government expenditure, household expenditure for education, and gross regional domestic product (GRDP) on the educational outcome, namely the education index. Data Envelopment Analysis (DEA) was selected as the methodology for analyzing the efficiency of local government expenditure on educational outcomes. The model assumed constant return to scale (CRS) and variable return to scale (VRS). Measurement of the effectiveness of government spending was calculated using panel data regression. To support the analyses, the current study used data from 38 districts and cities in East Java from 2007 to 2014. The results showed that government expenditure in the educational sector was relatively inefficient. Government Expenditure for Education (PPP) had no significant impact on the educational index, while Household Expenditure for -Education (PPRT) and GRDP per Capita had a positively significant impact on the Education Index (IP). This implies that government expenditure for the educational sector is not effective in improving the educational index.